Predator body sizes and habitat preferences predict predation rates in an agroecosystem - Rusch, Adrien; Birkhofer, Klaus; Bommarco, Riccardo; Smith, Henrik G.; Ekbom, Barbara (Basic and applied ecology, 2015)
Top-down control of pest populations by their natural enemies is a crucial ecosystem service supporting agricultural production. The relationship between predator community composition and predation rates of pests remains poorly investigated. A deeper understanding of the processes shaping interaction strength in agroecosystems is needed if we are to accurately predict natural pest control services. Functional traits in a community can provide insights into processes shaping community assembly and ecosystem functioning. Functional diversity indices can be constructed from a single trait, such as body length, or from the integration of multiple traits, such as body length, hunting mode and habitat preference. However, their performance in predicting ecosystem functioning and services remains largely unexplored. We used empirical data replicated at landscape scales to examine which component of ground-dwelling predator community structure (activity-density, species richness, evenness, taxonomic distinctness and functional diversity) of spiders, carabids and staphylinids best predicted predation rates of aphids in spring cereals. Functional diversity explained a greater part of variation in predation rates than any other taxonomic or activity-density component. Among the indices for functional diversity, single-trait indices better predicted variation in aphid predation rates compared with multiple-trait indices. In particular, we found that the community-average value of body-size of ground-dwelling predators was negatively related to predation rates of aphids, whereas the proportion of spiders with a preference for arable land was positively related to predation rates. Additional analyses of body-size distributions of ground-dwelling predators suggested that intraguild predation was a key process shaping the relationship between predator community composition and the level of aphid pest control. Considering the functional trait composition of communities provides a more mechanistic understanding of the processes shaping the strength of trophic interactions in terrestrial ecosystems, thus improving predictive power. Body-size distribution and habitat preference appear to be particularly valuable in predicting the level of natural pest control by ground-dwelling predators in an agroecosystem. Die Schädlingsbekämpfung durch natürliche Feinde ist eine wichtige ökosystemare Dienstleistung und trägt positiv zur landwirtschaftlichen Produktion bei. Der Zusammenhang zwischen der Zusammensetzung von Räubergemeinschaften und der Frassleistung an Schädlingspopulationen ist jedoch wenig untersucht. Ein besseres Verständnis der Prozesse welche Interaktionen zwischen natürlichen Feinden und Schädlingen bestimmen, ist für Vorhersagen von Schädlingskontroll-Leistungen wichtig. Die funktionellen Eigenschaften in Tiergemeinschaften können dabei Einblicke in Prozesse liefern und verschiedene Indizes, welche auf einzelnen oder mehreren Eigenschaften basieren, wurden für die Analyse von Gemeinschaften entwickelt. Beziehungen zwischen diesen Indizes und ökosystemaren Funktionen und Dienstleistungen wurden bisher jedoch nicht ausreichend untersucht. In dieser Studie wurden auf der Landschaftsebene replizierte, empirische Daten verwendet um Beziehungen zwischen der Gemeinschaftsstruktur (Aktivitätsdichte, Artenzahl, Äquität, taxonomische Verschiedenheit und funktionelle Diversität) von Spinnen, Lauf- und Kurzflügelkäfern und Frassleistungen an Blattlauspopulationen zu untersuchen. Die funktionelle Diversität erklärte den höchsten Anteil der Variation der Frassleistung und Indizes welche auf einzelnen Eigenschaften basierten waren dafür besser geeignet als multivariate Indizes. Der für Abundanzen von Räuber-Arten gewichtete Körpergrößenindex stand in einer negativen Beziehung zur Frassleistung an Blattläusen. Gemeinschaften mit einem hohen Anteil von Spinnen, die Agrarhabitate präferieren, zeigten eine hohe Frassleistung an Blattläusen. Zusätzliche Analysen der Körpergrößenverteilung in Räubergemeinschaften deuten außerdem darauf hin, dass Intragilde-Prädation ein wichtiger Prozesse, für die Bestimmung der natürlichen Kontrolle von Blattlauspopulationen ist. Eine Berücksichtigung der funktionellen Eigenschaften in Räubergemeinschaften ermöglicht ein verbessertes, mechanistisches Verständnis der Prozesse welche trophische Interaktionen in terrestrischen Ökosystemen beeinflussen. Sowohl die Berücksichtigung von Körpergrößenverteilungen als auch von Habitat-Präferenzen sind von besonderer Bedeutung für die Vorhersage der Schädlingskontroll-Leistung durch laufaktive generalistische Prädatoren im Agrarland.